7×[7⁴-7×(7³-7⁵:7³)]-7⁴=
Răspunsuri la întrebare
Răspuns de
0
Răspuns:
0
Explicație pas cu pas:
7×[7⁴ - 7 × (7³ - 7⁵ : 7³)] -7⁴ =
= 7×[7⁴ - 7 × (7³ - 7²)] -7⁴
= 7×[7⁴ - 7 × 7²(7 - 1)] -7⁴
= 7×(7⁴ - 7 × 7²×6) -7⁴
= 7×(7⁴ - 7³×6) -7⁴
= 7×7³(7 - 6) -7⁴
= 7⁴×1 -7⁴
= 7⁴ - 7⁴
= 0
Răspuns de
0
Răspuns:
0
Explicație pas cu pas:
7×[7⁴-7×(7³-7²)]-7⁴=
7×[7⁴-7×(7³-49)]-2401=
7×(7⁴-7⁴-343)-2401=
7×343-2401=
2401-2401=0
Alte întrebări interesante
Matematică,
8 ani în urmă
Matematică,
8 ani în urmă
Matematică,
8 ani în urmă
Matematică,
8 ani în urmă
Limba română,
8 ani în urmă
Matematică,
9 ani în urmă
Limba română,
9 ani în urmă
Limba română,
9 ani în urmă